Characteristics of Involuntarily Admitted Patients and Treatment Patterns Over a 21-Year Observation Period. Issue 4 (August 2018) - Welte, Anna-Sophia; Edlinger, Monika; Kemmler, Georg; Yalcin-Siedentopf, Nursen; Fleischhacker, W. Wolfgang; Hofer, Alex
Abstract: Background: Patients suffering from psychiatric disorders are often treated in locked psychiatric units owing to psychomotor agitation, hostility and aggressive behavior, or suicidality. Because of legal conditions, investigations of these acutely ill patients are difficult, and many studies do not represent real-life psychiatry . In Austria, admission to a locked psychiatric unit is regulated by a national law for involuntary admission, which came into effect in 1991. The current retrospective study investigated the management of patients who were admitted involuntarily to an academic treatment center after the inauguration of this law. Methods: Data collection comprised all admissions to a locked unit at the Department of Psychiatry, Psychotherapy and Psychosomatics of the Medical University Innsbruck in the years 1992, 1997, 2002, 2007, and 2012. Demographics, admission diagnosis, current danger posed to self or others, and the initial psychopharmacological intervention were assessed. Results: The rate of admissions to a locked unit increased significantly throughout the course of the study, and the length of stay decreased from 8.57 days in 1997 to 6.43 days in 2012. Most patients received medication orally. Dosage of antipsychotics and benzodiazepines decreased throughout the investigation period. Self-endangering patients were treated with somewhat (nonsignificantly) higher benzodiazepine and significantly lower antipsychotic mean doses than patients posing danger to others. Conclusions: Although dosage of medication was reduced, the duration of stay in a locked unit decreased significantly over the investigated years. These findings suggest that a carefully considered pharmacological treatment may be at least as effective as a more aggressive approach. Abstract : Supplemental digital content is available in the text.